(untitled) (Nigerian Journal of Technology, 2017)
This review assesses the impact of climate change on lake water resources in Sub-Saharan Africa(SSA). Two significant global water features with immense contribution to agriculture and socio-economic development of the region were analysed. Lake Victoria is the world second largest freshwater lake and Lake Chad the largest endoreic basin. These two great water bodies have been affected drastically by climate change and human influence. A significant shrinkage on Lake Chad was experienced with a decrease in water stored from in 1960s to less than in 2005. This effect abruptly receded Lake Chad from 25,000Km2 in the 1960s to 1350Km2 in 2005; while Lake Victoria experienced continual fluctuations from over a century; with evaporation rates varying between 1370mm to 1600mm, 90% of water loss which leads to peak fluctuation occurring in 1961. http://dx.doi.org/10.4314/njt.v36i2.42